Emotional balance and its relationship with athletic achievement motivation for volleyball players - Shaker Mahmood, Khalid (International Journal of Psychosocial Rehabilitation, 2020)
An aim of current research is to know the relationship between emotional equilibrium and the motivation of the player. The results show that the volleyball players have the motive for sporting achievement. There is a positive relationship between achievement motivation and emotional balance. The emotional balance scale and the mathematical achievement motivation scale can be used by researchers and scholars in this field. It is recommended that the inclusion of training programs for handball teams on training and procedures strengthen the motivation. The inclusion of training programs for handball teams on exercises and procedures to support and strengthen the manifestations of internal organization, social cohesion, movement cohesion, and interaction "" inside and outside the training units. It is necessary that trainers' awareness of psychological variables and their effects on the level of achievement and identifying the level of motivation of the handball teams using the scale in question during periods of the sports season and during the different roles of the league. Identify the level of internal organization aspects of the handball team players using the measures in question during periods of the sports season and during the different roles of the league. The coaches must pay attention to the mental preparation of the players in order to control the emotional arousal and the motivation of achievement and raise them to the optimal level that achieves the high levels. The necessity to rely on one of the mental training methods (according to the response of the players and the available capabilities) to reduce the degree of emotional arousal for the player and make it at the appropriate level (optimal arousal) The use of the two search measures on the players to know the psychological state and justify the behavior.